Ethical Eggs: Can Synthetic Biology Disrupt the Global Egg Production Industry? - Mankad, Aditi; Hobman, Elizabeth V.; Carter, Lucy; Tizard, Mark (Frontiers in Sustainable Food Systems, 2022)
Commercial egg production relies on the industry-accepted practice of culling day-old male chicks, which are a live by-product of the egg production industry. Researchers are exploring the use of a transgenic marker gene to allow early identification of male embryos in ovo at the point of lay, rather than upon hatching. Here we examine social acceptability of this biotechnology-enabled solution to sex selection, which addresses the key ethical issue of culling and improved sustainability of food systems. A national online survey (N = 1148) measured psychological factors influencing public support for the development of the technology and willingness to purchase eggs derived from the novel process. Most participants expressed at least a moderate intention to support the development of gene marking technology, with 1 in 5 people expressing strong support. Participants expressed moderate to high agreement that gene marking of chickens would: a) help reduce or eliminate the practice of culling male chicks in the egg-laying industry (response efficacy), and; b) that this new synbio approach to sex selection may be better than current methods of identifying and removing male chicks during egg production (relative advantage). Of those participants who consumed eggs, almost 60% reported they would be moderately to strongly willing to purchase eggs derived from the gene marking process. A partially-mediated path model comprising both intention to support and willingness to buy eggs (R2 = .78) showed that key factors involved in decision-making, in addition to response efficacy and relative advantage, were evaluative attitudes towards the technology (e.g., was the technology bad/good, risky/safe, unethical/ethical) and emotional reactions. These results suggest that consumers may be primarily basing their decisions and behavioural choices on how valuable they perceive the novel gene marking solution, reflecting on how it compares favourably to current culling practices, yielding a range of benefits such as higher animal welfare, improved sustainability, and reduced waste.